Traditional Knowledge on The Animal Utilization by The Hatam Tribe of Manokwari, West Papua Province - Sutarno, Simon; Qayim, Ibnul; Muhadiono, Ignatius; Purwanto, Yohanes; Zuhud, Ervizal A. M. (Biosaintifika: Journal of Biology & Biology Education, 2017)
Animal utilization in traditional community life is an integral part of traditional knowledge itself. This research aims to reveal the Hatam peoples traditional knowledge about the utilization of animals in their lives. The method used is the exploratory survey method. The respondents were determined purposively using the snowball sampling technique. The results showed that there are at least 55 species of animals commonly used by the Hatam people. Based on the forms of utilization, the animals can be divided into six groups: consumption, traditional medicine, specific meanings, traditional technology and arts, significant value, and traditional purposes. Wild animals are most widely used for the living needs of the Hatam people. The traditional hunt that is limited and the communal land ownership system (ulayat system) practiced by the Hatam people have indirectly helped preserve and ensure the availability of wildlife for the Hatam peoples needs. In addition to being a form of documentation of Hatam peoples traditional knowledge, the results of this research also have significance for the development of science especially in the field of ethnozoology. The form of interaction between Hatam people and animals revealed in this research can also serve as a reference for designing development policies related to the presence of Hatam people in the Arfak mountains.